PERUBAHAN SOSIAL BUDAYA MASYARAKAT DAN PERKEMBANGAN TEKNOLOGI DI ERA SAAT INI - Ahmad Faisal Fadhilah; Etty Ratnawati (PT. Intelek Cendikiawan Nusantara, 2024)
The socio-cultural changes in Indonesian society that have occurred in the last few decades have been greatly influenced by the development of communication technology. Information and communication technology (ICT) has changed the way people interact, communicate, and transact. This technological development not only accelerates access to information and the spread of culture, but also forms a new lifestyle that is more integrated with the digital world. In the Indonesian context, communication technology has played an important role in strengthening local cultural identity, facilitating education, and improving community welfare. However, challenges related to the gap in access to technology and the negative impact on traditional values are also concerns that need to be addressed.